2012
DOI: 10.1074/jbc.m112.393801
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens Alpha-toxin Recognizes the GM1a-TrkA Complex

Abstract: Background: Gangliosides are receptors for bacterial toxins. Results: Alpha-toxin from Clostridium perfringens specifically interacts with GM1a. Conclusion: Trp-84 and Tyr-85 of alpha-toxin are the residues that interact with GM1a, leading to activation of TrkA in A549 cells. Significance: These results define the role of GM1a-TrkA as a receptor for alpha-toxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 51 publications
1
43
0
1
Order By: Relevance
“…Therefore, direct disruption of the host cell membrane is not the only mechanism by which CPA causes cell lysis. It has also been shown that CPA activates the MEK/extracellular signal-regulated kinase (ERK) pathway and thereby induces oxidative stress in affected cells (36,37) and interleukin-8 (IL-8) production by stimulating both the ERK1/2 and p38 mitogen-activated protein kinase (MAPK) pathways (38). Recent studies suggested that CPA may induce signal transduction changes after binding to a ganglioside GM1 receptor (38).…”
Section: Chromosomally Encoded Toxinsmentioning
confidence: 99%
“…Therefore, direct disruption of the host cell membrane is not the only mechanism by which CPA causes cell lysis. It has also been shown that CPA activates the MEK/extracellular signal-regulated kinase (ERK) pathway and thereby induces oxidative stress in affected cells (36,37) and interleukin-8 (IL-8) production by stimulating both the ERK1/2 and p38 mitogen-activated protein kinase (MAPK) pathways (38). Recent studies suggested that CPA may induce signal transduction changes after binding to a ganglioside GM1 receptor (38).…”
Section: Chromosomally Encoded Toxinsmentioning
confidence: 99%
“…However, we have no answer to this proposition, because no solid surface covered by a single SO has been available. Recently, a plastics company developed sugar arrays to search for the binding targets of pathogenic factors (27,28).In the present study, we examined the binding and the gliding of M. mobile on plastic surfaces covered by uniform oligosaccharides, and concluded that the variations in sugar structures cause …”
mentioning
confidence: 99%
“…In addition to disrupting membrane phospholipids through phospholipase activity, α-toxin binding to GM1a triggers specific signaling events. The activation of a tyrosine kinase A (TrkA) [45] and the subsequent signaling cascade results in the release of tumor necrosis factor-α (TNF-α). The catastrophic events induced by α-toxin may in part be mediated by TNF-α signaling.…”
Section: Discussionmentioning
confidence: 99%